Phylogenetic position of African Vitrinidae: Old family groups unraveled. (14th July 2021) - Pfarrer, Beat; Rowson, Ben; Tattersfield, Peter; Neubert, Eike
Abstract: A phylogenetic investigation of genera and species of the semislug family Vitrinidae from Europe, East Africa, Arabia, and Macaronesia is presented. Two mitochondrial markers ( COI & 16S ) and a set of nuclear markers ( H3 & ITS2 ) were used in maximum likelihood (ML) and Bayesian inference (BI) analyses. The synopsis of DNA sequence data and anatomical data provide a first insight into the phylogenetic relationships of these groups. The existence of major groups comprising European, Macaronesian, and Arabian‐African genera is proven, however, their relationship remains unresolved. The sister‐group relationship between the Macaronesian radiation and a newly discovered East African genus Sanettivitrina nov. gen., perhaps a relic of this radiation, is demonstrated. The separation of the remaining East African Vitrinidae into two clades as hypothesized by earlier authors, viz. Arabivitrina Thiele, 1931 and Calidivitrina Pilsbry, 1919 could not be confirmed. The hitherto used generic definitions based on genital morphology are not able to explain the existence of at least five lineages in East Africa. Apparently, Arabivitrina and Calidivitrina morphotypes experienced several parallel losses of genital organ appendices. Abstract : A phylogenetic investigation of genera and species of the semislug family Vitrinidae from Europe, East Africa, Arabia, and Macaronesia is presented. Two mitochondrial markers ( COI & 16S ) and a set of nuclear markers (H3 & ITS2) were used in maximum likelihood (ML) and Bayesian inference (BI) analyses. With a "missing link, " Sanettivitrina scripta nov. gen. nov. sp., we found evidence for a direct connection of an ancient Macaronesian fauna within the East African fauna.